Synthesis, Characterization and Electrical Properties of a Composite of Topological Insulating Material: Bi2Te3-PANI. (2015) - Urkude, R.R.; Patil, P.T.; Kondawar, S.B.; Palikundwar, U.A.
Abstract: In the present work, we carried out a systematic study of structure, UV-Vis Spectra and surface conductivity of pure Bi2 Te3, pure Polyaniline (PANI) and Bi2 Te3 (5%)-PANI (95%) composite. Bi2 Te3 was synthesized by a method similar to solvothermal method, whereas, pure PANI and Bi2 Te3 -PANI composite were synthesized by a chemical oxidative method. The materials were structurally characterized and the electrical properties were investigated in the temperature range from room temperature to 100 °C. The electrical conductivity of the Bi2 Te3 -PANI composite is found to be higher than that of its pure constituents at all the temperatures. The enhancement in the surface conductivity may be due to the PANI generated ordered molecular arrangement of Bi2 Te3 in the Bi2 Te3 -PANI composite, as confirmed from powder x-ray diffraction, UV–vis spectral analysis.